Stream response to precipitation variability: a spectral view based on analysis and modelling of hydrological cycle components. Issue 7 (28th August 2014) - Markovic, D.; Koch, M.
Abstract Hydrological processes commonly exhibit long‐term persistence, also known as the 'Hurst phenomenon'. Here, we examine long‐term precipitation and streamflow time series from the Elbe River Basin to quantify differences in the spectral properties and in the Hurst parameter estimates (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjbskdhc4" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />H^</alternatives>) of the individual hydrological cycle components. Precipitation‐runoff modelling is performed for the Elbe River sub‐catchment Striegis using the Soil and Water Assessment Tool (SWAT). For 38 daily 50 years long streamflow time series from the Elbe River Basin, baseflow separation and spectral analysis is performed. The results show a spectral shift towards low‐frequency scales (>2 years) from precipitation to baseflow, with a parallel increase of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjbskdhgp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />H^</alternatives> from 0.52 (precipitation) to 0.65 (baseflow). The SWAT model is able to reproduce both, the main low‐frequency mode (≈7 yr.) and the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjbskdgwd" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />H^</alternatives> (0.62) of the observed Striegis River flow time series. The baseflow appears to be the main component which shapes the low‐frequency response and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjbskdgxx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />H^</alternatives> of streamflow in the Elbe River Basin to the input precipitation. This conclusion is further confirmed through PMWIN‐MODFLOW groundwater modelling of a hypothetic phreatic stream‐connected aquifer system that consists of various soils (sand, loamy sand and silt). A power shift towards lower frequencies and an increase of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjbskdgtc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />H^</alternatives> for the hydraulic heads is obtained, as the aquifer's lateral dimensions increase and its hydraulic conductivity decreases. The average <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjbskdgvw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />H^</alternatives> of the groundwater heads is 0.80, 0.90 and 1.0 for sand, loamy sand and silt aquifers, respectively. Copyright © 2014 John Wiley & Sons, Ltd.